Outcome comparison between transcatheter closure and surgical closure of atrial septum defect - Hussein Mohammed Rasool; Abed Noor Yousif; Abed Maysam Yousif; Akram Nabeeha Najatee (Acta Marisiensis - Seria Medica, 2025)
Introduction: Atrial septal defect (ASD) is a common congenital heart defect found in both children and adults, with potential serious complications if not addressed. Transcatheter device closure is a less invasive alternative to surgical correction, particularly for patients not suitable for the former.